THE ANALYSIS OF ORTHODONTIC CARE INDICATORS IN HEALTHCARE INSTITUTIONS OF DONETSK REGION - O.A. Udod; S.I. Dramaretska (Український стоматологічний альманах, 2023)
Actuality. The reform of the health care system affects the indicators of the provision of dental care in communally owned institutions.